269 views

Uploaded by Peter Fisher

- Curvature 24 Nov 2008
- Interval 29 Sep 2008
- Curvature 13 Nov 2008
- Doppler
- Airplane 3 Nov 2008
- AlphaCentauri
- The Subtle Art of Not Giving a F*ck: A Counterintuitive Approach to Living a Good Life
- Sapiens: A Brief History of Humankind
- The Unwinding: An Inner History of the New America
- Hidden Figures: The American Dream and the Untold Story of the Black Women Mathematicians Who Helped Win the Space Race
- Elon Musk: Tesla, SpaceX, and the Quest for a Fantastic Future
- Shoe Dog: A Memoir by the Creator of Nike
- Never Split the Difference: Negotiating As If Your Life Depended On It
- Maybe You Should Talk to Someone: A Therapist, HER Therapist, and Our Lives Revealed
- John Adams
- Devil in the Grove: Thurgood Marshall, the Groveland Boys, and the Dawn of a New America
- Grit: The Power of Passion and Perseverance
- Yes Please
- This Changes Everything: Capitalism vs. The Climate
- A Heartbreaking Work Of Staggering Genius: A Memoir Based on a True Story

You are on page 1of 1

033

Compton who first observed the scattering photon has a longer wavelength than the

incident photon. In recitation, we used momentum energy conservation to relate the shift

in wavelength to the scattering angle. The calculation took four blackboards as was

somewhat tedious.

This post shows how to carry out the calculation much more efficiently using four

vectors. The initial photon is denoted by the four vector K, the initial electron by P.

After the collision, K’ and P’ denote the photon and electron, respectively. Then, energy-

momentum conservation says P+K=P’+K’ which may be written P-P’=K’-K. Then,

square both sides:

2 2

( P − P ')

= ( K '− K )

P − 2PP '+ P ' = K 2 − 2KK '+ K '2

2 2

The last step makes use of P2=P’2=m2c4 and K2=K’2=0. To work out PP’ and KK’, we

need to write out the four vectors:

0 kc k 'c cosθ p 'c cos φ

0 0 k 'csin θ p 'csin φ

P= K= K'= P' =

0 0 0 0

2

mc kc k 'c E'

Notice I have used k to denote the momentum of the photon (not the wave number).

Then, PP ' = E ' mc2 and KK ' = k ' kc2 − k ' kc2 cosθ and we have

m 2 c 4 − E ' mc2 = −kk 'c 2 (1 − cosθ ) . Energy conservation gives E ' = mc2 + kc − k 'c and

kk '

we have m 2 c 4 − m 2 c 4 − mc 3 ( k − k ') = −kk 'c 2 (1 − cosθ ) → ( k − k ') = (1 − cosθ ) .

mc

h h

Finally, use k = to obtain λ '− λ = (1 − cosθ ) .

λ mc